2022
DOI: 10.1177/26330040211070295
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic angiogenesis in Buerger’s disease: reviewing the treatment landscape

Abstract: Thromboangiitis obliterans, also known as Buerger’s disease, is a rare inflammatory vasculitis that predominantly develops in smokers and characteristically affects the small- and medium-sized peripheral arteries and veins. Patients typically present with extremity claudication, but symptoms may progress to rest pain and tissue loss, especially in those unable to abstain from tobacco use. Unfortunately, traditional medical treatments are largely ineffective and due to the small caliber of affected vessels and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 112 publications
(158 reference statements)
0
7
0
Order By: Relevance
“…11 With current evidence, there are many types of treatments, both pharmacological and nonpharmacological, with the greatest evidence of results being the suspension of tobacco consumption. 2 The prognosis tends to be good for patients, although it has been reported that up to 70% of patients will experience an ischemic ulcer or necrosis. In some long-term studies it was reported that between 2.7 and 10.5% required major limb amputations; However, in a multicenter study of 224 patients, it was found that 34% of patients may require amputation 15 years after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation

Thromboangiitis obliterans: a review

Correa-Posada,
García-Velez,
Hurtado-Mosquera
et al. 2024
Int Surg J
“…11 With current evidence, there are many types of treatments, both pharmacological and nonpharmacological, with the greatest evidence of results being the suspension of tobacco consumption. 2 The prognosis tends to be good for patients, although it has been reported that up to 70% of patients will experience an ischemic ulcer or necrosis. In some long-term studies it was reported that between 2.7 and 10.5% required major limb amputations; However, in a multicenter study of 224 patients, it was found that 34% of patients may require amputation 15 years after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…1 Later, the disease was named after Leo Buerger, who in 1908 published a complete pathological description based on the amputation of a group of people, including smokers, with neuropathic pain, trophic changes in the skin and annexes such as distal coldness, loss of hair, onychodystrophy, with absence of posterior pedis and tibial pulses, lasting months to years, and which later presented with gangrene in the short term. 2,3 1919 results were found in SpringerLink, 1674 in Scopus, 1862 in PubMed and 5871 in ScienceDirect. A review of the articles found was carried out, the most current ones were analyzed in a period from 2002-2024 with emphasis on articles from the last 5 years, scientific articles from observational and analytical studies were included, with a total of 37 articles.…”
Section: Introductionmentioning
confidence: 99%

Thromboangiitis obliterans: a review

Correa-Posada,
García-Velez,
Hurtado-Mosquera
et al. 2024
Int Surg J
“…TAO progression will eventually lead to limb amputation. Therefore, the ideal treatment modality for TAO is still undecided and controversial [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, most are ineffective (12). Angiogenesis stimulation (13), and sympathectomy (14)are prominent surgical options in these patients, but the distal ischemic conditions have almost made these cases ineffective in the main treatment.…”
Section: Introductionmentioning
confidence: 99%